A Learning Health System Approach to Cancer Survivorship Care Among LGBTQ+ Communities. Issue 1 (7th December 2022) - Dunne, Will; Adebayo, Nihmotallahi; Danner, Sankirtana; Post, Sharon; O'Brian, Catherine; Tom, Laura; Osei, Cassandra; Blum, Cori; Rivera, Juan; Molina, Elena; Trosman, Julia; Weldon, Christine; et al.
Abstract : PURPOSE: Lesbian, gay, bisexual, transgender, and queer (LGBTQ+) individuals who receive primary care services at community health centers are often referred to external specialty care centers after cancer diagnosis, upon which primary care services are disrupted and may be discontinued because of gaps in communication between primary and oncologic care providers. This qualitative study evaluated barriers and facilitators to effective care coordination for LGBTQ+ patients with cancer and the utility of a novel cancer care coordination tool to mitigate identified barriers. MATERIALS AND METHODS: Semistructured interviews with LGBTQ+ cancer survivors, caregivers to LGBTQ+ persons, clinical team members who provide care to LGBTQ+ patients, and members of community-based organizations that work with LGBTQ+ patients were conducted. Interview analysis was a multistage process, wherein a constant comparison approach was used. Transcripts were reviewed and coded using Atlas.ti Cloud. RESULTS: A total of 26 individuals were interviewed: 10 patients, four caregivers, 10 clinical care team members, and two community organization representatives. Interview analysis yielded insight regarding (1) LGBTQ+ patient experiences engaging with primary and oncologic care at the clinic level and (2) perceptions of patient-provider and provider-provider communication and coordination. CONCLUSION: Interview findings indicate a need for further development of interventions aimed at improving care coordination, patient experience, and outcomes in the cancer care continuum for LGBTQ+ patients. Learning health systems, like the one studied, show great potential for contributing to the development of such interventions.